3D wave-resolving simulation of sandbar migration. (December 2022) - Marchesiello, Patrick; Chauchat, Julien; Shafiei, Hassan; Almar, Rafael; Benshila, Rachid; Dumas, Franck; Debreu, Laurent
Abstract: The problem of sandbar migration on the storm timescale is revisited with a 3D wave-resolving hydro-sedimentary model. The latter presents an intermediate approach between expensive wave-resolving two-phase flow models and highly parametrized wave-averaged models. Innovative features include the use of weakly compressible assumptions in the hydrodynamics and morphological acceleration of bed changes to speed up numerical simulations. The model accurately simulates the successive offshore and onshore bar migration observed in a large-scale flume experiment in response to wave forcing representing storm and post-storm (recovery) conditions. The diagnosis of sand transport and the analysis of an ensemble-averaged asymmetric wave cycle reveal the migration mechanisms in each phase. In all cases, sediment resuspension is impacted by breaker-induced turbulence, while sediment transport and bed evolution are primarily the result of the undertow distribution – the breaker-induced seaward undercurrent – across the sandbar. There is also a significant contribution from asymmetric wave-related onshore fluxes, due to greater mobilization and currents during the wave crest period. Highlights: A 3D free-surface wave-resolving model is applied to nearshore sandbar migration. The model simulates a flume experiment in response to storm and post-storm wave conditions. Results are analyzed with wave-mean sediment budgets and a composite wave cycle diagnostic. The net sediment transport results primarily from the undertow distribution across the sandbar. During recovery conditions, wave asymmetry contributes to the onshore bar migration.